2020
DOI: 10.5455/medarh.2020.74.363-368
|View full text |Cite
|
Sign up to set email alerts
|

Age Distribution of Clinical Symptoms, Isolation, Co-morbidities and Case Fatality Rate of COVID-19 Cases in Najaf City, Iraq

Abstract: Introduction: The first case of coronavirus disease 2019 (COVID-19) in holy Najaf city in February 22, 2020. The outbreak then rose up all over Iraq from 519 cases and 20 deaths in June 2, 2020 to 3484 cases and 72 deaths per day in August 10, 2020 per 24 hours. Aim: The aim of the study is to describe the distribution of confirmed cases by age, demographic factors, isolation, comorbidities and case fatality rate. Methods: Prospectively collected and analyzed data on patients with laboratory-confirmed 2019-nCo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 18 publications
(23 reference statements)
0
9
0
Order By: Relevance
“…Analysis of the collected data revealed that the COVID-19 mortality rate was higher in older adults, particularly men. Studies conducted by Abdel Ghaffar et al in Egypt 12 and by Al-Mudhaffer et al in Iraq 13 showed that male gender was associated with higher risk of mortality compared to female. They also found that older age and comorbidities were significant predictors of mortality among COVID-19 patients.…”
Section: Discussionmentioning
confidence: 94%
“…Analysis of the collected data revealed that the COVID-19 mortality rate was higher in older adults, particularly men. Studies conducted by Abdel Ghaffar et al in Egypt 12 and by Al-Mudhaffer et al in Iraq 13 showed that male gender was associated with higher risk of mortality compared to female. They also found that older age and comorbidities were significant predictors of mortality among COVID-19 patients.…”
Section: Discussionmentioning
confidence: 94%
“…The results of the statistical analysis showed that there is an effect of infection with SARS-COV2 virus on the parameters of total protein, albumin, and globulin, as shown in Table (2). The results showed a significant decrease at the level (p < 0.05) after infection with the virus in the concentration of total protein and albumin in the blood serum of infected people in Baghdad governorate, and their values were 65.9 and 39.5 (g / l), respectively, compared with their values in the healthy group, which were 69.2 and 42.7 (g/l), respectively, while the globulin concentration was close to its value in the healthy group, which was 26.5 (g/l).…”
Section: Effect On the Level Of Total Protein Albumin And Globulinmentioning
confidence: 99%
“…This virus spread throughout the world and caused COVID-19 disease [1]. As Iraq reported its first confirmed cases of SARS-CoV-2 virus on February 22, 2020 in the city of Najaf, and this case was confirmed after laboratory tests conducted during the same day, and the outbreak of the disease began in all other governorates, especially the capital, Baghdad, where the number reached Alif on the fifth day of April [2]. 1262 (2023) 062044 IOP Publishing doi:10.1088/1755-1315/1262/6/062044 2 Good nutrition creates an environment in which the immune system is able to respond appropriately to infection, in contrast to malnutrition, which creates an environment in which the immune system cannot respond well.…”
Section: Introductionmentioning
confidence: 99%
“…Healthcare workers (HCWs) reported higher levels of stress because of the high workload, putting themselves at risk, and concerns of spreading infection to their families and friends [ 89 ]. HCWs from Iraq were more likely to report anxiety, depression, and stress than others in the Middle East region.…”
Section: Case Studymentioning
confidence: 99%